Gender Development And Empowerment Effect On Income Inequality And Poverty - Suparman SUPARMAN (International Journal of Environmental, Sustainability, and Social Science, 2021)
This research aims to know the impact of development and gender empowerment on the condition of income inequality and poverty in Indonesia. This study uses data on the gender development index (IPG), gender empowerment index (IDG), income inequality or Gini ratio/GR), and the number of poor people (POV) according to data from 34 provinces in Indonesia for the period 2015-2020. The analytical method used is the Granger causality test and panel regression model (common effect model/CEM, fixed effect model/FEM), random effect model/REM). The analysis results found that the gender development index (GIP) had a positive and significant effect on the number of poor people (POV) in Indonesia.